Thermal properties of flame retardant cotton fabric grafted by dimethyl methacryloyloxyethyl phosphate - Xing Tie-Ling (Thermal Science, 2012)
Thermal properties of flame retardant cotton fabric grafted by dimethyl methacryloy-loxyethyl phosphate were investigated by the atom transfer radical polymerization method. Thermal gravimetric analysis was used to explore the thermal decomposition mode of flamed retardant cotton fabric. The weight loss rate of the flamed retardant cotton was bigger than that of the control cotton fabric, and a more final residual char of flamed retardant cotton was also observed. Flammability tests were used to study the flame retardance property of the flame retardant cotton fabric. The results showed that flamed retardant cotton fabric with 16.8% of weight gain could keep good flame retardance. Scanning electron microscope pictures were applied to investigate the morphology of residual char of the flame retardant samples.